A joint clearing model for the participation of renewable energy and energy storage in the frequency modulation ancillary service market considering performance differences - Wang, Chang; Jiang, Yu; Guo, Hao; Bai, Kun; Zhang, Xiangyu; Wang, Aoer (Frontiers in Energy Research, 2023)
The increasing growth in installed capacity for renewable energy sources has progressively replaced traditional thermal power units as synchronous power contributors. This transition has led to a reduction in system inertia and resources for frequency regulation, creating a need for renewable energy and energy storage to participate in system frequency modulation (FM). Empirical studies indicate that the current market mechanism for frequency modulation auxiliary services, which predominantly rely on thermal power, is suboptimal for leveraging the unique capabilities of diverse frequency modulation resources. This inadequacy hinders the power industry's pursuit of the "dual carbon" goals-carbon neutrality and carbon peak. Hence, this paper proposes a joint clearing model for the involvement of renewable energy and energy storage in the frequency modulation auxiliary service market. It considers performance differences and employs the Analytic hierarchy process (AHP) to guide the optimization of the weights of frequency modulation performance indicators for various frequency modulation resources. This approach allows renewable energy, energy storage, and thermal power to maximize the benefits of their own differentiated advantages in various frequency modulation performance indicators. Consequently, this fosters an increased share of renewable energy within the system while ensuring frequency stability, thereby expediting the achievement of the power industry's "dual carbon" goals. Finally, computational analyses substantiate that the proposed joint clearing model, accounting for performance differentials, can enhance the renewable energy share in the system and simultaneously reduce the societal costs associated with frequency modulation services.